Factor Analysis and Psychometric Validation of the Body Image Disturbance Questionnaire in an Australian Undergraduate Sample. (14th June 2017) - Collison, James; Mahlberg, Justin
Abstract : Objective: Body image disturbance encompasses various cognitive and behavioural states originating from a distressing, negative evaluation of one's appearance. It is broader than negative body image, comprising not only dissatisfaction but also distress and dysfunction, and is a core feature of body dysmorphic disorder (BDD). This study had two broad aims: to establish normative values for body image disturbance within an Australian population and to examine the factor structure and psychometric properties of the Body Image Disturbance Questionnaire (BIDQ). Method: Australian undergraduate students ( N = 950, 744 female) from Western Sydney completed the BIDQ, along with measures of clinical psychopathology, self‐esteem, and functional impairment. Results: The BIDQ displayed good internal consistency and predictable concurrent relationships with measures of depression, anxiety, stress, self‐esteem, and functional impairment. It also yielded a single latent construct, while higher scores were noted among participants who screened positively for BDD. Conclusions: BIDQ scores for this sample differ to those originally reported, which may reflect sample differences or cultural variation. These values provide a more accurate and reliable guide for clinicians using the BIDQ in Australia than previously available. Overall, the BIDQ demonstrates good psychometric efficacy in an undergraduate sample, although future research should validate the measure among wider clinical and community populations.